Improving Energy Efficiency and Autonomy Through the Development of a Hybrid Battery–Supercapacitor System in Electromobility - Michalakis Kotsias; Georgios Kontogogos; Spyridon Angelopoulos; Evangelos Hristoforou (Energies)
This study focuses on the development of a hybrid battery-supercapacitor system aimed at enhancing energy efficiency and autonomy in electromobility. The energy supply system of an electric vehicle must ensure high performance and autonomy, even after numerous battery life cycles. Previous approaches to hybrid systems that combine batteries and supercapacitors focus on reducing power losses by relying on controllers that evaluate the state of charge (SOC) of the energy sources to determine which one should provide power at any given time. These systems typically use a controller that monitors only the SOC of the battery and supercapacitor. In contrast, our study introduces an innovative controller that not only evaluates the SOC of both energy sources but also incorporates the current of the electric motor, taking into account its operational state. This approach allows for a more accurate representation of energy consumption and motor performance, providing significant advantages in terms of energy efficiency, extended battery life, and improved performance under high motor loads, which are characteristic of modern electric vehicle requirements. The current paper encompasses both experimental and simulated results, indicating that the hybrid approach provides significant advantages, such as improved energy autonomy, extended battery life as the primary energy source, and enhanced performance at high motor speeds that stress the battery.